The efficacy and safety of Xuefu Zhuyu Decoction combined with Mifepristone in the treatment of uterine leiomyoma: A systematic review and meta-analysis. (5th December 2021) - Shi, Shasha; Ye, Qiaobo; Yu, Chenghao; Peng, Fu
Abstract: Ethnopharmacological relevance: Uterine leiomyoma (UL) is a common severe gynecological issue. In China, Xuefu Zhuyu Decoction (XFZYD), combined with Mifepristone, is widely used in the treatment of UL. However, their combined effectiveness and safety for this purpose have not yet been explored. Aim of the study: This systematic review aims to evaluate the effectiveness and safety of XFZYD combined with Mifepristone as a method of treatment for UL. Materials and methods: We searched the following 7 databases: 3 English medical databases (PubMed, EMBASE, Cochrane Library), and 4 Chinese medical databases (Chinese Biomedical Literature Database (CBM), Chinese National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database (VIP), and the Wanfang database). The primary outcome was the effect of XFZYD combined with Mifepristone on the effective rate, uterine leiomyoma volume (ULV), and uterine volume (UV) of uterine leiomyoma. Bias risk was assessed using the Cochrane risk of bias tool. The software RevMan5 was used to evaluate the quality of the included studies and process the data. Results: The 11 studies included in this systematic review were all undertaken in China, with a total of 902 participants. The meta-analysis of XFZYD combined with Mifepristone compared with Mifepristone alone showed that the effective rate (RR 1.20, 95% confidence interval (CI): 1.14–1.27, P < 0.00001), ULV (SMD -1.60, 95% CI: 2.11 to −1.08, P < 0.00001), and UV (SMD -1.65, 95% CI: 1.85 to −1.44, P < 0.00001) in the primary outcomes, and estradiol (E2) (MD -51.81, 95% CI: 69.68 to −33.94, P < 0.00001), luteinizing hormone (LH) (MD -3.09, 95% CI: 3.58 to −2.60, P < 0.00001), follicle stimulating hormone (FSH) (MD -1.09, 95% CI: 1.86 to −0.31, P = 0.006), progesterone (P) (MD -3.55, 95% CI: 4.54 to −2.55, P < 0.00001), and adverse events (RR 0.55, 95% CI: 0.34–0.89), P = 0.01) in the secondary outcomes were significantly reduced, and the data were statistically significant. The subgroups of ULV, E2, and FSH showed that the treatment time might not have been the heterogeneous source of ULV and FSH, but was the heterogeneous source of E2. Sensitivity analysis was carried out on the 3 outcome indicators, and the results were relatively stable after excluding one reference for each indicator. Conclusion: There is some encouraging evidence that the combination of XFZYD and Mifepristone can benefit patients by treating UL. However, because of research shortcomings such as lacking allocation concealment and blindness, this study's results should be treated with caution. In order to verify the advantages of this method, it is necessary to carry out further large-scale randomized controlled trials. Highlights: Data obtained from 11 studies with 902 subjects were meta-analyzed. XF ZY D and Mifepristone can benefit patients by treating Uterine leiomyoma. The efficacy of XF ZY D combined with Mifepristone in the treatment of Uterine leiomyoma was superior to Mifepristone.